Dinamika Perubahan Sosial Dan Hukum Islam - Azhari, Fathurrahman (IAIN Ponorogo, 2016)
Abstract: The Dynamics of Social Change and Islamic Law are related each other in making a change. In the one hand,Â social changeis caused by the Islamic law, but on the other hand, the change of Islamic law itself is causedby the social changes. The existence of Islamic law, which was broughtÂ by Rasulullah Saw, had clearly changed the social community at that time;the changes started from jahiliyyah societyera that strongly heldÂ theirÂ tradition to the Islamic societyera that held Islamic law.By the same token, Islamic law had also made a change due to social changes. According to juries-prudency of Islamic law(regulations made by fukaha/Islamic cleric) that thechange of the fatwa (advice) was caused by the change of the periode, place, situation (niat) and tradition